Size and Charge Stability of Oil Bodies from Peanut - Lihua Hao; Fusheng Chen; Yimiao Xia; Lifen Zhang; Ying Xin (Journal of Chemistry)
In order to offer scientific bases for the application of oil bodies from peanut in food, this research was undertaken to study the size and charge stability of oil bodies from five peanut varieties. It showed that the mean diameter of oil bodies from yuhua9719 and yuhua9830 is obviously larger than yuhua23, yuhua27, and yuhua9502 in the peanut cell. Moreover, the analysis of diameter distribution of oil bodies also showed that the median diameter of oil bodies increased dramatically in the order of yuhua9719 > yuhua9830 > yuhua23 > yuhua27 > yuhua9502 after aqueous extraction. The charge stability of oil bodies from peanut was observed with zeta (ζ) potential measurements, which indicated that charge properties and the absolute value of oil bodies from five peanut varieties were significantly affected by pH and salt concentration, but the degree of influence is different. Of the five peanut varieties, yuhua27 and yuhua9830 possessed excellent charge stability (ζ-potential > 35 mV) in neutral microenvironment without salt concentration.